2017
DOI: 10.1111/adb.12503
|View full text |Cite
|
Sign up to set email alerts
|

Naltrexone ameliorates functional network abnormalities in alcohol‐dependent individuals

Abstract: Naltrexone, an opioid receptor antagonist, is commonly used as a relapse prevention medication in alcohol and opiate addiction, but its efficacy and the mechanisms underpinning its clinical usefulness are not well characterized. In the current study, we examined the effects of 50‐mg naltrexone compared with placebo on neural network changes associated with substance dependence in 21 alcohol and 36 poly‐drug‐dependent individuals compared with 36 healthy volunteers. Graph theoretic and network‐based statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 55 publications
5
28
0
Order By: Relevance
“…The few naltrexone studies that have examined functional connectivity vary in analysis parameters, populations of interest, and study designs. These studies have shown that naltrexone modulates connectivity between ACC and hippocampus as a function of childhood adversity during an emotional priming task among alcohol-dependent individuals (Savulich et al, 2017), and that naltrexone improves local network efficiency in alcohol dependent individuals, reaching that of healthy controls (Morris et al, 2018). Most notably, in a study of methamphetamine users, naltrexone decreased connectivity between precuneus and sensorimontor regions and increased connectivity between dorsal striatum and precuneus with frontal regions (Courtney et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…The few naltrexone studies that have examined functional connectivity vary in analysis parameters, populations of interest, and study designs. These studies have shown that naltrexone modulates connectivity between ACC and hippocampus as a function of childhood adversity during an emotional priming task among alcohol-dependent individuals (Savulich et al, 2017), and that naltrexone improves local network efficiency in alcohol dependent individuals, reaching that of healthy controls (Morris et al, 2018). Most notably, in a study of methamphetamine users, naltrexone decreased connectivity between precuneus and sensorimontor regions and increased connectivity between dorsal striatum and precuneus with frontal regions (Courtney et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…With regard to pharmacotherapies, while their action on cortical excitability and brain plasticity have been studies, it will be also critical to define how medications currently used for AD modulate brain activity and connectivity. For example, naltrexone, a medication commonly used in patients with alcohol and opioid use disorders, has been shown to modulate brain connectivity (Morris et al, 2018;Elton et al, 2019). Since NIBS also has a modulatory effect on brain connectivity, particularly when applied to network nodes (Eldaief et al, 2011), future research should investigate whether these effects can be combined in a synergistic fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging studies of alcohol use disorder demonstrate the effects of naltrexone on brain function and connectivity (Lukas et al, 2013; Mann et al, 2014; Morris et al, 2017; Spagnolo et al, 2014). We extend these results to individuals with MA use disorder and show a reduction in striatolimbic RSFC in the XR-NTX group compared to a Placebo group.…”
Section: Discussionmentioning
confidence: 99%